Study of Science Learning Based on Scientific Literacy in Improving Critical Thinking: A Scoping Review - Bramastia Bramastia; Satutik Rahayu (Jurnal Penelitian Pendidikan IPA, 2023)
Facing and following increasingly sophisticated technological developments in science learning studies, both pupils and students must increase scientific literacy to improve critical thinking. Critical thinking skills will encourage students to understand problems and create alternative problem solutions with problem solving stages, namely clarification, assessment, inference and strategy. This research aims to explore the Study of Science Learning Based on Scientific Literacy in Improving Critical Thinking. The research was conducted using a scoping review approach. A scoping review is typically used to map the existing literature on a defined topic in terms of the volume, nature, and characteristics of key studies. The results of the scoping review analysis found several problems such as the low level of science learning regarding scientific literature so that pupils and students are unable to identify problematic issues and scientific evidence due to a lack of practicing skills in conducting scientific literature. The impact that occurs is that the ability to think critically decreases. Therefore, various efforts are being made, one of which is that pupils and students must have concepts to connect science, science learning websites, focus on specific knowledge, be able to design relevant indicators, have the ability to translate into critical, systematic and anticipatory actions, students' critical thinking skills , school location, and problem-based learning model